Purine 5′, 8-cyclo-2′-deoxynucleoside lesions: formation by radical stress and repair in human breast epithelial cancer cells. (4th May 2017) - Krokidis, Marios G.; Terzidis, Michael A.; Efthimiadou, Eleni; Zervou, Sevasti-Kiriaki; Kordas, George; Papadopoulos, Kyriakos; Hiskia, Anastasia; Kletsas, Dimitris; Chatgilialoglu, Chryssostomos
Abstract: 5′, 8-Cyclo-2′-deoxyadenosine (cdA) and 5′, 8-cyclo-2′-deoxyguanosine (cdG) in their two diastereomeric forms, 5′ S and 5′ R, are tandem lesions produced by the attack of hydroxyl radicals to the purine moieties of DNA. Their formation has been found to challenge the cells' repair machinery, initiating the nucleotide excision repair (NER) for restoring the genome integrity. The involvement of oxidatively induced DNA damage in carcinogenesis and the reduced capacity of some cancer cell lines to repair oxidised DNA base lesions, intrigued us to investigate the implication of these lesions in breast cancer, the most frequently occurring cancer in women. Using liquid chromatography tandem mass spectrometry (LC-MS/MS), we measured the levels of diastereomeric cdA's and cdG's in estrogen receptor-alpha positive (ER-α) MCF-7 and triple negative MDA-MB-231 breast cancer cell lines before and after exposure to two different conditions: ionising radiations and hydrogen peroxide, followed by an interval period to allow DNA repair. An increase at the measured levels of all four lesions, i.e. 5′ S -cdA, 5′ R -cdA, 5′ S -cdG and 5′ R -cdG, was observed either after γ -irradiation (5 Gy dose) or hydrogen peroxide treatment (300 μM) compared to the untreated cells (control), independently from the length of the interval period for repair. For comparison reasons, we also measured the levels of 8-oxo-2′-deoxyadenosine (8-oxo-dA), a well-known oxidatively induced DNA damage lesion and base excision repair (BER) substrate. The collected data indicate that MCF-7 and MDA-MB-231 breast cancer cells are highly susceptible to radiation-induced DNA damage, being mainly defective in the repair of these lesions.